2020
DOI: 10.1186/s13046-019-1514-3
|View full text |Cite
|
Sign up to set email alerts
|

Complement C3 overexpression activates JAK2/STAT3 pathway and correlates with gastric cancer progression

Abstract: Background: Localized C3 deposition is a well-known factor of inflammation. However, its role in oncoprogression of gastric cancer (GC) remains obscured. This study aims to explore the prognostic value of C3 deposition and to elucidate the mechanism of C3-related oncoprogression for GC. Methods: From August to December 2013, 106 GC patients were prospectively included. The regional expression of C3 and other effectors in gastric tissues were detected by WB, IHC, qRT-PCR and other tests. The correlation of loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 48 publications
(45 reference statements)
0
57
2
Order By: Relevance
“…(ii) Autocrine regulation of complement transcripts/secretion by complement complexes or cleavage products, which are only produced if the SNP is present, could be imaginable. Complement components or complement cleavage products can activate cellular signaling pathways via specific receptors [ 63 , 64 , 65 ], which can result in increased or reduced transcription of complement components by associated transcription factors [ 66 , 67 , 68 ]. As we showed the secretion of complement components and presents of complement activation products as well as of receptors in hpRPE cells an autocrine regulation of complement is speculatively possible.…”
Section: Discussionmentioning
confidence: 99%
“…(ii) Autocrine regulation of complement transcripts/secretion by complement complexes or cleavage products, which are only produced if the SNP is present, could be imaginable. Complement components or complement cleavage products can activate cellular signaling pathways via specific receptors [ 63 , 64 , 65 ], which can result in increased or reduced transcription of complement components by associated transcription factors [ 66 , 67 , 68 ]. As we showed the secretion of complement components and presents of complement activation products as well as of receptors in hpRPE cells an autocrine regulation of complement is speculatively possible.…”
Section: Discussionmentioning
confidence: 99%
“…Altered protein expression of complement components has also been described. In gastric cancer, tumours exhibit enhanced deposition of C3 and C3a relative to adjacent healthy tissue, with high C3 deposition observed to correlate with worse 5 year OS [155]. Evidence suggests that C3 deposits may activate JAK2/STAT3 to enhance tumour growth [155].…”
Section: Human Studiesmentioning
confidence: 99%
“…Yuan et al study found that high complement C3 (C3) deposition activates JAK2/STAT3 pathway correlates with in gastric cancer progression and was identified as an independent prognostic factor of poor overall survival [22]. C3 plays a role of diagnostic signature including achieved a predictive error of 12.8% and a Generalized Brier Score of 0.108 lung adenocarcinoma and squamous cell carcinoma [23].…”
Section: Discussionmentioning
confidence: 99%